2022
DOI: 10.3390/cancers14092139
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of HER3 Expression in Patients with Cervical Cancer

Abstract: HER3 has been recognized to have an oncogenic role in various types of cancer. However, its prognostic significance has not been elucidated in cervical cancer. The aim of this study was to investigate the prognostic significance of HER3 expression in cervical cancer using immunohistochemistry (IHC). HER3 immunohistochemical staining was performed on the tumor tissue samples of 336 cervical cancer patients. The association between the clinicopathological characteristics and patient survival analysis was assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…HER3 plays many roles in cancer cells, including mediating cell transformation and tumor malignancy [45,46]. Cancer patients with high HER3 expression are reported to have poorer prognoses in several cancer types [10][11][12][13][14][15]. Our results indicate that increased HER3 expression at recurrence may be associated with an inferior prognosis (Fig.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…HER3 plays many roles in cancer cells, including mediating cell transformation and tumor malignancy [45,46]. Cancer patients with high HER3 expression are reported to have poorer prognoses in several cancer types [10][11][12][13][14][15]. Our results indicate that increased HER3 expression at recurrence may be associated with an inferior prognosis (Fig.…”
Section: Discussionmentioning
confidence: 71%
“…In gynecological cancers, the incidence of HER3 overexpression was reported to be 41.3-67.5% for ovarian cancer [5,27,28], 30% for endometrial cancer [29], and 31.0-74.7% for cervical cancer [15,[30][31][32]. However, most studies have only reported the incidence of HER3 expression at initial diagnosis, while that at recurrent diagnosis was not evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…HER3 plays many roles in cancer cells, including mediating cell transformation and tumor malignancy [ 46 , 47 ]. Cancer patients with high HER3 expression are reported to have poorer prognoses in several cancer types [ 10 15 ]. Our results indicate that increased HER3 expression at recurrence may be associated with an inferior prognosis (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It heterodimerizes with receptor tyrosine kinases to activate oncogenic signaling via the the phosphatidylinositol 3-kinase/protein kinase B pathway [ 1 , 2 ]. Overexpression of HER3 is observed in several cancers [ 3 9 ] and is associated with inferior prognosis [ 10 15 ]. In addition, several reports have suggested a pathogenic role for HER3 in mechanisms underlying primary or acquired resistance to EGFR inhibitors [ 16 18 ] and anti-HER2 therapies [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation